Parenting Stress of Mothers Having Children with Thalassemia: Parenting stress (Journal of Preventive and Social Medicine, 2020)
Background: Parents of children with thalassemia faces numerous challenges while coping various problems arises from the disease.Objective: The study was conductedto assess parenting stress of the mothers having children with thalassemia.Materials and Methods: This was a cross sectional study conducted amongmothers having children with thalassemia. A total of 253 mothers were included in this study conveniently.Data were collected by face to face interview by using a semi-structured questionnaire. Data analysiswere done by SPSS software. Level of stress was measured by using a modified parenting stress scale. The study was carried out during January to December 2016.Place and period of study: This study was conducted in International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b), Dhaka Shishu Hospital thalassemia center, Thalassemia foundation hospital and Bangabandhu Sheikh Mujib Medical University.Results: The study revealed that 25-34 years age group was more (83.4%). Majorityofthemothers was Muslim (97%), married (95%), educated up to SSC (64%), house wife (87%). Average monthly family income of the mothers was 26257 BDT and most of them were living in nuclear family (68%). Majority of the mothers had 2 children (82.2%), maximum was within 1-10 years age group (65.2%) and bearingchild within 15-24 years (64%). Most of the mothers had male children (63%), received antenatal checkup (84%) and normal delivery (70%) at hospital (58%). Complication during pregnancy was found in few mothers (15%) and included malnutrition with anemia. Majority of the children were diagnosed thalassemia within 2 years of age (79.8%) and physical complications included reduced hemoglobin level and physical activity. Few thalassemic children had splenectomy (13%), majority of the children’s condition was not improved (72%). Most of the respondents visited hospital once in a month (46%). Among all mothers, few had social support (28%) and greater part received financial support (84%). Majority of the mothers faced moderate level stress (52.2%). Mean of parenting stress was 40.16(±8.07). Minimum and maximum score of parenting stress was 22 and 59 respectively.Conclusion: The parents having children with Thalassemia are burdened and under stress because of the chronic nature of the illness. All the findings suggests that time decisions with proper psychological supports and appropriate managements system can overcome the long term sufferings of the patients and thus reduce the stress of parents.JOPSOM 2019; 38(2): 22-29